Preparation method of n-type ZrNiSn alloy and Ni nanoparticle compounded thermoelectric material

By compounding ZrNiSn alloy with Ni nanoparticles and adopting high-energy ball milling and spark plasma sintering, the full Heusler phase of ZrNi2Sn is generated, which solves the problem of high thermal conductivity of ZrNiSn alloy, improves the power factor and reduces thermal conductivity, and realizes the industrial preparation of high-performance thermoelectric materials.

CN120696407APending Publication Date: 2025-09-26NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510927078.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

The existing ZrNiSn alloy has high thermal conductivity, which limits the improvement of its thermoelectric performance. In addition, the preparation process is sensitive to the thermoelectric properties of the material, making it difficult to prepare high-performance thermoelectric materials.

Method used

By preparing a composite of ZrNiSn alloy and Ni nanoparticles, high-energy ball milling and spark plasma sintering are used to generate a ZrNi2Sn full-Heusler phase, which improves the electrical conductivity and reduces the lattice thermal conductivity, thereby achieving coordinated regulation of electroacoustic transport.

Benefits of technology

The power factor of the material is improved, the thermal conductivity is reduced, high-throughput preparation and cost savings are achieved, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120696407A_ABST
    Figure CN120696407A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an n-type ZrNiSn alloy and Ni nanoparticle compounded thermoelectric material, and particularly relates to the technical field of thermoelectric materials. The preparation method of the n-type ZrNiSn alloy and Ni nanoparticle composite thermoelectric material comprises the following steps: firstly, preparing a ZrNiSn alloy ingot, and crushing and grinding the ZrNiSn alloy ingot to obtain ZrNiSn alloy ingot coarse powder; mixing with Ni nanoparticles, and performing high-energy ball milling to obtain composite powder; the composite powder is subjected to spark plasma sintering, the thermoelectric material ZrNi1 + xSn formed by compounding the n-type ZrNiSn alloy and the Ni nanoparticles is obtained, and x ranges from 0.02 to 0.1; the high-flux preparation of the ZrNiSn-based nano composite material is realized, the ZrNi2Sn full Heusler phase is generated, the electrical conductivity and power factor of the material are improved, the thermal conductivity is reduced at the same time, and the collaborative regulation and control of electro-acoustic transport are realized; the preparation method provided by the invention is simple to operate, relatively short in process period and suitable for industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric materials, and in particular to a method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles. Background Art

[0002] With the intensifying energy crisis and increasingly severe environmental pollution, improving energy efficiency is a key path to addressing the dual challenges of energy shortages and environmental pollution. Waste heat from industrial processes, vehicle emissions, and solar radiation can be used as a valuable resource to generate clean electricity. Thermoelectric devices can directly convert heat into electricity and are applicable in waste heat recovery, thermoelectric power generation, refrigeration, sensors, wearable devices, building energy conservation, military and medical applications, and other fields, improving energy efficiency.

[0003] The thermoelectric performance of thermoelectric materials is determined by the dimensionless thermoelectric figure of merit ZT, which is defined as ZT = S 2 s T / ( k e + κ L ), where S is the Seebeck coefficient, is the conductivity, T is the absolute temperature, k e is the electronic thermal conductivity, κ L is the lattice thermal conductivity. Half-Heusler (HH) alloys are ternary intermetallic compounds with the general chemical formula ABX and a face-centered cubic structure of MgAgAs. They can be used as thermoelectric materials in medium- and high-temperature applications, boasting excellent mechanical properties, high thermal stability, and environmentally friendly composition. HH alloys have high power factors, for example, ZrNiSn alloys have a power factor of 30-36 μW cm at 873 K. -1 K -2 However, HH alloys also have high intrinsic thermal conductivity, and ZrNiSn alloys at room temperature k 4~10 W m -1 K - 1. Improving the thermoelectric performance of HH alloys relies on the coordinated regulation of electroacoustic transport behavior. Incorporating nanoparticles into HH alloys is an important method for improving their ZT. However, the thermoelectric properties of HH nanocomposites are sensitive to their microstructure and phase composition, and the preparation process has a significant impact on the material's thermoelectric properties. Therefore, exploring and optimizing the preparation methods of HH nanocomposites is essential for obtaining high-performance thermoelectric materials. Summary of the Invention

[0004] The present invention aims to provide a method for preparing a thermoelectric material composed of an n-type ZrNiSn alloy and Ni nanoparticles, which facilitates composition control and saves costs. The ZrNiSn-based nanocomposite material provided by the present invention has a high power factor and low thermal conductivity.

[0005] To achieve the above object, the present invention provides a method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles, the preparation method comprising the following steps: Step 1: preparing a ZrNiSn alloy ingot, crushing and grinding it to obtain a coarse ZrNiSn alloy ingot powder; Step 2: mixing the ZrNiSn alloy ingot coarse powder with Ni nanoparticles, and obtaining a composite powder after high-energy ball milling; Step 3: The composite powder is subjected to spark plasma sintering to obtain a thermoelectric material ZrNiSn composite of n-type ZrNiSn alloy and Ni nanoparticles. 1+x Sn, where x=0.02~0.1.

[0006] Preferably, in the process of preparing the ZrNiSn alloy ingot, Zr, Ni, and Sn elemental raw materials are weighed according to an atomic ratio of 1:1:1, and are placed in a melting furnace in the order of low-melting-point element at the bottom and high-melting-point element at the top, and arc melting is performed under an argon protective atmosphere to obtain a ZrNiSn alloy ingot.

[0007] Preferably, the Zr single-substance raw material is irregular block particles with a particle size of 1 to 6 mm; the Ni single-substance raw material is cylindrical particles with a diameter of 4 to 5 mm and a height of 3 to 6 mm; the Sn single-substance raw material is spherical particles with a diameter of 1 to 1.5 mm.

[0008] Preferably, the arc melting current is 200-400 mA; and the number of flipping times during the melting process is 3-5 times.

[0009] Preferably, the particle size of the ZrNiSn alloy ingot coarse powder in step 1 is 0.1-1 mm.

[0010] Preferably, the particle size of the Ni nanoparticles in step 2 is 50 nm, and the atomic ratio of the Ni nanoparticles to the ZrNiSn alloy ingot coarse powder is 2% to 10%.

[0011] Preferably, the ball-to-material ratio of the high-energy ball milling in step 2 is 5:1, the rotation speed is 600-900 r / min, and the ball milling time is 3-4 h, wherein the can inversion operation needs to be performed once every 1-2 h of ball milling.

[0012] Preferably, the particle size of the composite powder in step 2 is 0.5-2 μm.

[0013] Preferably, the spark plasma sintering process in step three is as follows: starting from room temperature, heating at a rate of 40-60 ° C / min to an intermediate temperature of 850-920 ° C, then heating at a rate of 10-20 ° C / min to a sintering temperature of 930-960 ° C, keeping warm for 10-20 minutes, then cooling at a rate of 30-60 ° C / min to 600-650 ° C, and then cooling to room temperature at a rate of 30-60 ° C / min. The pressure is constant at 45-55 MPa during the entire sintering process.

[0014] Preferably, the spark plasma sintering is performed in a graphite mold.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention realizes the high-throughput preparation of ZrNiSn-based nanocomposite materials by compounding ZrNiSn alloy with Ni nanoparticles; Ni nanoparticles and ZrNiSn alloy undergo chemical reaction during spark plasma sintering to generate ZrNi2Sn full Heusler phase, thereby improving the electrical conductivity and power factor of the material. 1.02 The power factor of Sn at 873 K is 46.11 μW cm -1 K -2 , which is 30.4% higher than that of ZrNiSn. Due to the scattering of phonons by the half-Heusler and full-Heusler phase interfaces, the lattice thermal conductivity of the material decreases. 1.02 The thermal conductivity of Sn at 873 K is 4.38 W m -1 K -1 , which is 10.3% lower than that of ZrNiSn, and finally realizes the coordinated regulation of electroacoustic transport; the preparation method provided by the present invention is simple to operate, has a short process cycle, and is suitable for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings of the embodiments will be briefly described below. It should be noted that the drawings described below only relate to some embodiments of the present disclosure and are not intended to limit the present disclosure. Figure 1 The ZrNi provided by the present invention 1+x XRD patterns of Sn (x=0-0.1) thermoelectric materials in comparative examples and examples.

[0017] Figure 2 The ZrNi provided by the present invention 1.1 Conductivity diagram of Sn thermoelectric materials in comparative examples and examples.

[0018] Figure 3 The ZrNi provided by the present invention1+x Conductivity diagram of Sn (x = 0-0.1) thermoelectric materials for comparative examples and examples.

[0019] Figure 4 The ZrNi provided by the present invention 1.1 Seebeck coefficient diagram of Sn thermoelectric materials in comparative examples and examples.

[0020] Figure 5 The ZrNi provided by the present invention 1+x Seebeck coefficient diagram of Sn (x = 0-0.1) thermoelectric materials for comparative examples and examples.

[0021] Figure 6 The ZrNi provided by the present invention 1.1 Power factor diagram of Sn thermoelectric material in comparative example and embodiment.

[0022] Figure 7 The ZrNi provided by the present invention 1+x Power factor diagram of Sn (x = 0-0.1) thermoelectric materials, comparative examples and examples.

[0023] Figure 8 The ZrNi provided by the present invention 1.1 Thermal conductivity diagram of Sn thermoelectric material in comparative example and embodiment.

[0024] Figure 9 The ZrNi provided by the present invention 1+x Thermal conductivity diagram of Sn (x = 0-0.1) thermoelectric materials for comparative examples and examples.

[0025] Figure 10 The ZrNi provided by the present invention 1+x Lattice thermal conductivity diagram of Sn (x = 0-0.1) thermoelectric materials for comparative examples and examples.

[0026] Figure 11 The ZrNi provided by the present invention 1.1 Thermoelectric figure of merit diagrams of Sn thermoelectric materials for comparative examples and embodiments.

[0027] Figure 12 The ZrNi provided by the present invention 1+x Thermoelectric figure of merit diagrams of Sn (x=0-0.1) thermoelectric materials for comparative examples and examples. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present disclosure more clear, the technical solutions of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.

[0029] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the subject matter of the present disclosure belongs. It will be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the specification and the relevant art, and will not be interpreted in an idealized or overly formal manner unless otherwise explicitly defined herein. As used herein, a statement that two or more parts are "connected" or "coupled" together shall mean that the parts are joined together either directly or through one or more intermediate components.

[0030] References to "embodiments" herein mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiment" in various places in the specification does not necessarily refer to the same embodiment, nor does it necessarily refer to independent or alternative embodiments that are mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0031] The present invention provides a method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles, the preparation method comprising the following steps: Step 1: preparing a ZrNiSn alloy ingot, crushing and grinding it to obtain a coarse ZrNiSn alloy ingot powder; Specifically, Zr, Ni, and Sn elemental raw materials are weighed according to an atomic ratio of 1:1:1, and are placed in a melting furnace in the order of low melting point element at the bottom and high melting point element at the top, and arc melting is performed under an argon protective atmosphere. The arc melting current is preferably 200-400 mA, for example, 200 mA, 250 mA, 300 mA, 350 mA, and 400 mA; the number of flippings during the melting process is preferably 3-5 times, for example, 3 times, 4 times, and 5 times, to obtain a ZrNiSn alloy ingot, wherein the Zr elemental raw material is an irregular block particle with a particle size of 1-6 mm; the Ni elemental raw material is a cylindrical particle with a diameter of 4-5 mm and a height of 3-6 mm; the Sn elemental raw material is a spherical particle with a diameter of 1-1.5 mm; the ZrNiSn alloy ingot is coarsely ground into a particle size of preferably 0.1-1 mm using a mortar under atmospheric conditions. The ZrNiSn alloy ingot coarse powder may have a particle size of 0.1 mm, 0.3 mm, 0.5 mm, 0.7 mm, 0.8 mm, or 1 mm, for example.

[0032] Step 2: mixing the ZrNiSn alloy ingot coarse powder with Ni nanoparticles, and obtaining a composite powder after high-energy ball milling; Specifically, the atomic ratio of the Ni nanoparticles to the ZrNiSn alloy ingot coarse powder is 2% to 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%. The Ni nanoparticles are weighed and placed in a ball mill in a glove box under argon protection conditions for high-energy ball milling. The ball-to-material ratio is 5:1, and the rotation speed is preferably 600 to 900 r / min, for example, 600 r / min, 700 r / min, 800 r / min, and 900 r / min. The ball milling time is preferably 3 to 4 h, for example, 3 h, 3.5 h, and 4 h. The can is inverted every 1 to 2 h of ball milling, and the powder adhering to the wall is loosened in the glove box to obtain a composite powder with a particle size of preferably 0.5 to 2 μm, for example, 0.5 μm, 0.8 μm, 1.2 μm, 1.5 μm, 1.8 μm, and 2 μm.

[0033] Step 3: The composite powder is subjected to spark plasma sintering to obtain a thermoelectric material ZrNiSn composite of n-type ZrNiSn alloy and Ni nanoparticles. 1+x Sn, wherein x=0.02~0.1 is preferred, for example, it can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1; Specifically, the composite powder is placed in a graphite mold for spark plasma sintering, starting from room temperature, preferably at a rate of 40-60°C / min, for example, 40°C / min, 50°C / min, 60°C / min, to a preferred intermediate temperature of 850-920°C, for example, 850°C, 870°C, 900°C, 920°C, and then at a rate of 10-20°C / min to a preferred sintering temperature of 930-960°C, for example, 93 0℃, 940℃, 950℃, 960℃, the holding time is preferably 10~20min, for example, 10min, 15min, 20min, then cooled at a rate of 30~60℃ / min, preferably to 600~650℃, for example, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, and then cooled to room temperature at a rate of 30~60℃ / min. The pressure is constant during the entire sintering process, preferably 45~55 MPa, for example, 45MPa, 50MPa, 55MPa.

[0034] The following describes the specific embodiments: Example 1 Take x=0.1 to prepare ZrNi 1.1 Sn thermoelectric material; Step 1: Taking ZrNiSn as the nominal composition, weigh Zr, Ni, and Sn elemental raw materials in an atomic ratio of 1:1:1, with the low-melting-point element at the bottom and the high-melting-point element at the top. Use a 100 mA melting current for the initial smelting. After the surface is completely melted, increase the current to 400 mA and turn on magnetic stirring. After four flipping and melting, obtain a ZrNiSn alloy ingot with uniform composition; crush the ZrNiSn alloy ingot and coarsely grind it into a powder with a particle size of 1 mm in a mortar under atmospheric conditions; Step 2: In a glove box under argon protection, 10 at.% nano-Ni powder and the ground ZrNiSn powder were weighed according to the atomic ratio and placed in a ball mill. Under the conditions of a ball-to-material ratio of 5:1, a rotation speed of 900 r / min, and a ball milling time of 3 h (the ball milling needs to be turned over once in the glove box every 1 h), ZrNiSn with a particle size of 1.5 μm was obtained by ball milling. 1.1 Sn composite powder.

[0035] Step 3: Place the composite powder in a graphite mold, heat it to 920°C for 10 minutes, then heat it to 950°C at a rate of 50°C / min, keep it warm for 15 minutes, cool it to 600°C for 10 minutes, and then cool it to room temperature with the furnace. The pressure is kept at 50 MPa throughout the process to obtain the nanocomposite thermoelectric material ZrNi 1.1 Sn.

[0036] Example 2 Take x=0.06 to prepare ZrNi 1.06 Sn thermoelectric material; Step 1: Taking ZrNiSn as the nominal composition, weigh Zr, Ni, and Sn elemental raw materials in an atomic ratio of 1:1:1, with the low-melting-point element at the bottom and the high-melting-point element at the top. Use a 100 mA melting current for the initial smelting. After the surface is completely melted, increase the current to 400 mA and turn on magnetic stirring. After four flipping and melting, obtain a ZrNiSn alloy ingot with uniform composition; crush the ZrNiSn alloy ingot and coarsely grind it into a powder with a particle size of 1 mm in a mortar under atmospheric conditions; Step 2: In a glove box under argon protection, weigh 6 at.% nano-Ni powder and the ground ZrNiSn powder according to the atomic ratio and place them in a ball mill. Under the conditions of ball-to-material ratio of 5:1, rotation speed of 900 r / min, and ball milling time of 3 h (the ball mill needs to be turned over once in the glove box every 1 h of ball milling), ZrNiSn with a particle size of 1.5 μm is obtained by ball milling. 1.1 Sn composite powder.

[0037] Step 3: Place the composite powder in a graphite mold, heat it to 920°C for 10 minutes, then heat it to 950°C at a rate of 50°C / min, keep it warm for 15 minutes, cool it to 600°C for 10 minutes, and then cool it to room temperature with the furnace. The pressure is kept at 50 MPa throughout the process to obtain the nanocomposite thermoelectric material ZrNi 1.06 Sn.

[0038] Example 3 Take x=0.02 to prepare ZrNi 1.06 Sn thermoelectric material; Step 1: Taking ZrNiSn as the nominal composition, weigh Zr, Ni, and Sn elemental raw materials in an atomic ratio of 1:1:1, with the low-melting-point element at the bottom and the high-melting-point element at the top. Use a 100 mA melting current for the initial smelting. After the surface is completely melted, increase the current to 400 mA and turn on magnetic stirring. After four flipping and melting, obtain a ZrNiSn alloy ingot with uniform composition; crush the ZrNiSn alloy ingot and coarsely grind it into a powder with a particle size of 1 mm in a mortar under atmospheric conditions; Step 2: In a glove box under argon protection, weigh 2 at.% nano-Ni powder and the ground ZrNiSn powder according to the atomic ratio and place them in a ball mill. Under the conditions of ball-to-material ratio of 5:1, rotation speed of 900 r / min, and ball milling time of 3 h (the ball mill needs to be turned over once in the glove box every 1 h of ball milling), ZrNiSn with a particle size of 1.5 μm is obtained by ball milling. 1.1 Sn composite powder.

[0039] Step 3: Place the composite powder in a graphite mold, heat it to 920°C for 10 minutes, then heat it to 950°C at a rate of 50°C / min, keep it warm for 15 minutes, cool it to 600°C for 10 minutes, and then cool it to room temperature with the furnace. The pressure is kept at 50 MPa throughout the process to obtain the nanocomposite thermoelectric material ZrNi 1.02 Sn.

[0040] Comparative Example 1 Preparation of ZrNiSn thermoelectric materials; Step 1: Taking ZrNiSn as the nominal composition, weigh Zr, Ni, and Sn elemental raw materials in an atomic ratio of 1:1:1, with the low-melting-point element at the bottom and the high-melting-point element at the top. Use a 100 mA melting current for the initial smelting. After the surface is completely melted, increase the current to 400 mA and turn on magnetic stirring. After four flipping and melting, obtain a ZrNiSn alloy ingot with uniform composition; crush the ZrNiSn alloy ingot and coarsely grind it into a powder with a particle size of 1 mm in a mortar under atmospheric conditions; Step 2: In a glove box under argon protection, the ground ZrNiSn powder was placed in a ball mill, and ball milled to obtain ZrNiSn powder with a particle size of 1.5 μm at a ball-to-material ratio of 5:1, a rotation speed of 900 r / min, and a ball milling time of 3 h (the ball mill needs to be turned over once in the glove box every 1 h of ball milling).

[0041] Step 3: Place the powder in a graphite mold, heat it to 920°C for 10 minutes, then heat it to 950°C at a rate of 50°C / min, keep it warm for 15 minutes, cool it to 600°C for 10 minutes, and then cool it to room temperature with the furnace. The pressure is maintained at 50 MPa throughout the process to obtain the thermoelectric material ZrNiSn.

[0042] Comparative Example 2 Preparation of ZrNi 1.1 Sn thermoelectric material; Step 1: ZrNi 1.1 Sn is the nominal composition. Zr, Ni, and Sn are weighed in an atomic ratio of 1:1.1:1, with the low-melting-point element at the bottom and the high-melting-point element at the top. A 100 mA melting current is used for the initial melting. After the surface is completely melted, the current is increased to 400 mA, and magnetic stirring is turned on. After four flip meltings, ZrNi with uniform composition is obtained. 1.1 Sn alloy ingot; ZrNi 1.1 The Sn alloy ingots were crushed and coarsely ground into powder with a particle size of 1 mm using a mortar under atmospheric conditions; Step 2: In a glove box under argon protection, grind the ZrNi 1.1Sn powder was placed in a ball mill, and ZrNi with a particle size of 1.5 μm was obtained by ball milling at a ball-to-material ratio of 5:1, a rotation speed of 900 r / min, and a ball milling time of 3 h (the jar needs to be turned over once every 1 h in the glove box). 1.1 Sn powder.

[0043] Step 3: Place the powder in a graphite mold, heat it to 920°C for 10 minutes, then heat it to 950°C at a rate of 50°C / min, keep it warm for 15 minutes, cool it to 600°C for 10 minutes, and then cool it to room temperature with the furnace. The pressure is kept at 50 MPa throughout the process to obtain the thermoelectric material ZrNi 1.1 Sn.

[0044] Comparative Example 3 ZrNi 1.1 Sn is the nominal component, and Zr, Ni, and Sn single-element raw material powders are weighed at an atomic ratio of 1:1.1:1, with a particle size of 45 μm. They are placed in a ball mill and ball-to-material ratio of 5:1, a rotation speed of 900 r / min, and a ball milling time of 3 h (the ball mill needs to be turned over once in the glove box every 1 h of ball milling) to obtain powders with a particle size of 10-30 μm.

[0045] The powder was placed in a graphite mold, heated to 920°C for 13 minutes, then heated to 1000°C at a rate of 50°C / min, kept warm for 15 minutes, cooled to 6500°C for 10 minutes, and then cooled to room temperature with the furnace. The pressure was maintained at 50 MPa throughout the process to obtain the thermoelectric material ZrNi 1.1 Sn.

[0046] Figure 1 ZrNi 1+x The XRD patterns of Sn (x = 0-0.1) thermoelectric materials in the comparative examples and examples. The main diffraction peaks of Examples 1-3 and Comparative Examples 1-3 are consistent with the standard PDF card of ZrNiSn, indicating that the ZrNiSn phase with MgAgAs structure is formed in all samples. 1.1 In Example 1 and Comparative Examples 2 and 3 of Sn, weak diffraction peaks appeared at 2θ=41°, 60°, and 74°, which were analyzed to be full Heusler (FH) phase ZrNi2Sn. This is because the excess Ni element induced the FH phase in ZrNi 1.1 Precipitation in Sn alloys. In Example 3, no obvious FH phase diffraction peaks appear because its Ni content is low, resulting in the FH phase content being less than the accuracy range of XRD detection. There are faint impurity peaks at 2θ = 29° and 42° in Comparative Example 3. Comparison with the PDF card confirms that the impurity phase is Ni3Sn2.

[0047] Figure 2ZrNi 1.1 Conductivity plot of Sn thermoelectric materials for comparative examples and examples. The conductivity of all alloys increases with temperature, demonstrating intrinsic semiconductor properties. Within the temperature range of 300 K to 773 K, Comparative Example 3 exhibits higher conductivity than Examples 1 and 2. Above 773 K, the conductivity of Comparative Example 2 continues to increase and surpasses that of Comparative Example 3. Example 1 exhibits the lowest conductivity over the entire temperature range.

[0048] Figure 3 ZrNi 1+x Conductivity plots for Sn (x = 0-0.1) thermoelectric materials for comparative and exemplary embodiments. As the Ni content increases, the conductivity increases. This is because more full-Heusler phases or interstitial Ni atoms precipitate with the addition of Ni, increasing the material's carrier concentration.

[0049] Figure 4 ZrNi 1.1 Seebeck coefficient diagram of Sn thermoelectric material comparison example and example. The Seebeck coefficients of Example 1, Comparative Example 2, and Comparative Example 3 are negative, indicating that the HH alloy is an n-type semiconductor. In the temperature range of 300 K to 873 K, the absolute values ​​of the Seebeck coefficient (|S|) are as follows from large to small: Example 1 > Comparative Example 2 > Comparative Example 3. The Seebeck coefficients of the three samples vary slightly with temperature. The Seebeck coefficients of Example 1 and Comparative Example 2 vary less with temperature, while the S temperature dependence curve of Comparative Example 3 is steeper and reaches a higher peak temperature. This is because the larger carrier concentration in Comparative Example 3 suppresses the generation of the bipolar effect.

[0050] Figure 5 ZrNi 1+x Power factor diagram of Sn (x = 0 ~ 0.1) thermoelectric material comparison example and embodiment. 1+x In the Sn alloy, as the Ni content increases from 0.02 to 0.1, the Seebeck coefficient decreases, which is completely opposite to the relative order of conductivity. Example 3 has an excellent Seebeck coefficient, with its |S| significantly higher than that of the other samples. In addition, the |S| of Example 3 is slightly higher than that of Comparative Example 1, which is due to the energy filtering effect at the interface between the nano-FH phase and the HH matrix.

[0051] Figure 6 ZrNi 1.1 Power factor plots for Sn thermoelectric materials, comparative examples, and examples. The power factor of all alloys increases with increasing temperature, with Comparative Example 3 exhibiting the lowest power factor within the tested temperature range. This is due to the significantly lower Seebeck coefficient, which significantly degrades the power factor. Example 1 and Comparative Example 2 exhibit similarly high power factors, thanks to their higher conductivity and highest Seebeck coefficient, respectively.

[0052] Figure 7 ZrNi 1+x Power factor plot for Sn (x = 0-0.1) thermoelectric materials, comparative examples and examples. As the Ni content increases from x = 0.02 to 0.1, the power factor decreases. Example 3 achieves the highest power factor within the tested temperature range due to its high Seebeck coefficient. Furthermore, Comparative Example 1 has a lower power factor due to its lowest Seebeck coefficient.

[0053] Figure 8 ZrNi 1.1 Thermal conductivity plot of Sn thermoelectric materials for comparative and exemplary embodiments. The thermal conductivity of Examples 1, 1, and 2 decreases slowly with increasing temperature. Above 773 K, the thermal conductivity shows a slow upward trend, attributed to the bipolar effect. The thermal conductivity of the alloy in Comparative Example 3 is significantly higher than that of Examples 1 and 2.

[0054] Figure 9 ZrNi 1+x Thermal conductivity of Sn (x = 0-0.1) alloys compared to the examples. Compared to Comparative Example 1, the addition of Ni nanoparticles significantly reduces the thermal conductivity of the alloy, and this reduction is more pronounced at low temperatures.

[0055] Figure 10 ZrNi 1+x Lattice thermal conductivity plots for Sn (x = 0-0.1) thermoelectric materials, including comparative examples and examples. The lattice thermal conductivity of all samples decreases with increasing temperature due to increased lattice vibrations and enhanced phonon scattering. Compared to Comparative Example 1, the lattice thermal conductivity of all examples decreases, with Example 2 exhibiting the lowest lattice thermal conductivity.

[0056] Figure 11 ZrNi 1.1 Figure of thermoelectric merit for the Sn thermoelectric material comparison example and the example. Example 1 and Comparative Example 2 have similar high ZT values ​​within the test range, with ZT values ​​of 0.74 and 0.77 at 873 K, respectively, demonstrating that Example 1 can achieve similar thermoelectric performance as Comparative Example 2 over the entire temperature range. Comparative Example 3 has a ZT value of 0.44 at 873 K, which is due to its higher thermal conductivity and lower power factor. Compared with Comparative Example 2, Example 1 can achieve high-throughput preparation of thermoelectric materials by adding different amounts of Ni nanoparticles during high-energy ball milling, which can quickly adjust the alloy composition, shorten the preparation process, and save costs.

[0057] Figure 12 ZrNi 1+xFigures of thermoelectric figures of merit for Sn (x = 0-0.1) thermoelectric materials, comparing comparative examples and examples. Example 3 reaches its maximum ZT value of 0.91 at 873 K, a 42.18% improvement over Comparative Example 1 and approximately 22.97% over Example 1. This demonstrates that the nanocomposite strategy of the present invention can effectively enhance the thermoelectric performance of HH alloys.

[0058] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles, characterized in that: The preparation method comprises the following steps: Step 1: preparing a ZrNiSn alloy ingot, crushing and grinding it to obtain a coarse ZrNiSn alloy ingot powder; Step 2: mixing the ZrNiSn alloy ingot coarse powder with Ni nanoparticles, and obtaining a composite powder after high-energy ball milling; Step 3: The composite powder is subjected to spark plasma sintering to obtain a thermoelectric material ZrNiSn composite of n-type ZrNiSn alloy and Ni nanoparticles. 1+x Sn, where x=0.02~0.

1.

2. The method for preparing a thermoelectric material composed of an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: In the process of preparing the ZrNiSn alloy ingot, Zr, Ni, and Sn elemental raw materials are weighed according to an atomic ratio of 1:1:1, and are placed in a melting furnace in the order of low-melting-point element at the bottom and high-melting-point element at the top. Arc melting is performed under an argon protective atmosphere to obtain a ZrNiSn alloy ingot.

3. The method for preparing a thermoelectric material composite of an n-type ZrNiSn alloy and Ni nanoparticles according to claim 2, characterized in that: The Zr single-substance raw material is irregular block particles with a particle size of 1 to 6 mm; the Ni single-substance raw material is cylindrical particles with a diameter of 4 to 5 mm and a height of 3 to 6 mm; the Sn single-substance raw material is spherical particles with a diameter of 1 to 1.5 mm.

4. The method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles according to claim 2, characterized in that: The arc melting current is 200-400 mA; the number of flipping times during the melting process is 3-5 times.

5. The method for preparing a thermoelectric material composed of an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: The particle size of the ZrNiSn alloy ingot coarse powder in step 1 is 0.1-1 mm.

6. The method for preparing a thermoelectric material composed of an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: The particle size of the Ni nanoparticles in step 2 is 50 nm, and the atomic ratio of the Ni nanoparticles to the ZrNiSn alloy ingot coarse powder is 2% to 10%.

7. The method for preparing a thermoelectric material composed of an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: The ball-to-material ratio of the high-energy ball milling in step 2 is 5:1, the rotation speed is 600-900 r / min, and the ball milling time is 3-4 h, wherein the can is turned over once every 1-2 h of ball milling.

8. The method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: The particle size of the composite powder in step 2 is 0.5-2 μm.

9. The method for preparing a thermoelectric material composited with an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: The spark plasma sintering process described in step 3 is as follows: starting from room temperature, heating at a rate of 40-60 ° C / min to an intermediate temperature of 850-920 ° C, then heating at a rate of 10-20 ° C / min to a sintering temperature of 930-960 ° C, keeping warm for 10-20 minutes, then cooling at a rate of 30-60 ° C / min to 600-650 ° C, and then cooling to room temperature at a rate of 30-60 ° C / min. The pressure is constant at 45-55 MPa during the entire sintering process.

10. The method for preparing a thermoelectric material composed of an n-type ZrNiSn alloy and Ni nanoparticles according to claim 1, characterized in that: The spark plasma sintering is carried out in a graphite mold.